An oral history of Atlantis : stories - Park, Ed, 1970- (Random House, 2025)
"In "Machine City," a college student's role in a friend's movie causes lines to blur between his character and his true self. In "Slide to Unlock," a man comes to terms with his life, via the passwords he struggles to remember in a moment of extremis. And in "Weird Menace," a director and faded movie star discuss science fiction, memory, and lost loves on a commentary track for a film from the '80s that neither seems to remember all that well. In Ed Park's utterly original collection, An Oral History of Atlantis, characters question the fleetingness of youth and art, reckon with the consequences of the everyday, and find solace in the absurd, the beautiful, and the sublime. Throughout, Park deploys his trademark wit to create a world both strikingly recognizable and delightfully other. All together, these fifteen stories have much to say about the meaning-and transitory nature-of our lives. And they are proof positive that Ed Park is one of the most insightful and imaginative writers working today." --